Two dimensional hierarchical architectures fabricated by the self-assembly of poly(3-hexylthiophene)-b-polyethylene glycol. Issue 46 (14th November 2022) - Qi, Rui; Zhu, Yulin; Han, Liang; Wang, Meijing; He, Feng
Abstract : 2D multi-layered hierarchical architectures, ball-like micelles, flower-like aggregates and nanoribbons were fabricated by the self-assembly of poly(3-hexylthiophene)(P3HT)- b -polyethylene glycol with a short P3HT chain in alcohol solvents. Abstract : Fabrication of nanomaterials by hierarchical self-assembly has attracted increasing interest, but controlling the sophisticated structures of hierarchical architectures is still challenging. Herein, we have developed a diblock copolymer, poly(3-hexylthiophene) (P3HT)- b -poly(ethylene glycol) (PEG) with a short P3HT chain. In i-PrOH, ultrathin 2D micelles and 2D hierarchical architectures containing multiple 2D lamellar structures can be fabricated by the hierarchical self-assembly of this diblock copolymer through a heating, cooling and aging process. The number of layers in the 2D hierarchical architectures can be tailored by controlling the polymer concentration. The π–π stacking interaction plays a key role in the formation of the hierarchical micelles. The morphologies of the nanostructures are dramatically influenced by the solvent polarity. Ball-like micelles, flower-like aggregates and nanoribbons can be prepared in methanol, ethanol and isobutanol. This study offers a new means to prepare hierarchical architectures.